TRADE UNION RECOGNITION IN MALAYSIA: LEGAL ISSUES (UUM Journal of Legal Studies, 2020)
In Malaysia, the Federal Constitution protects the worker’s enjoyment as to freedom of association, in particular, the right to form and join the trade union. However, due to security purposes, various restrictions have been imposed on trade union activities. The recognition process is currently showing a decline in the number of recognition awards due to the government’s policy. This paper examines the legal issues and challenges confronting the trade union in the recognition process in Malaysia. This study adopted the qualitative approach to analyse the statutory procedures and cases relating to the issue. Interviews were conducted with the Department of Industrial Relations, Malaysia and the Department of Trade Union Affairs, Malaysia to obtain their opinion on the recognition process. It is suggested that the Malaysian government should abolish the employer’s recognition; provide a statutory definition on the managerial, executive, confidential and security positions; establish an independent administrative trade union board and ratify the Convention Concerning Freedom of Association and Protection of the Right to Organise Convention No. 87.